This is not a Love Song. Du détournement des médias télévisés par John Lydon : du spectacle au Spectacle - Christophe Becker (Criminocorpus)
As the leader of the Sex Pistols under the name Johnny Rotten, British musician John Lydon has long been a provocateur. He’s considered from very early on that the media in general, and most of all television, were a natural enemy although he understands their functioning perfectly well and uses them to develop his own political message. We will study the persona Lydon has been building and inhabiting since 1976. We will see how the singer turns the notion of the polite and harmless star upside down in order to highlight the vacuity of the media-crazed world and of contemporary British society, and how he uses an apparent varnish of rudeness, of stupidity, of bad education, cynicism and bad taste to elaborate on a political and artistic discourse that is the exact opposite of what he’s chosen to show on the screen.